2022
DOI: 10.1038/s41598-022-12480-2
|View full text |Cite
|
Sign up to set email alerts
|

Apparent regional differences in the spectrum of BARD1 pathogenic variants in Spanish population and importance of copy number variants

Abstract: Only up to 25% of the cases in which there is a familial aggregation of breast and/or ovarian cancer are explained by germline mutations in the well-known BRCA1 and BRCA2 high-risk genes. Recently, the BRCA1-associated ring domain (BARD1), that partners BRCA1 in DNA repair, has been confirmed as a moderate-risk breast cancer susceptibility gene. Taking advantage of next-generation sequencing techniques, and with the purpose of defining the whole spectrum of possible pathogenic variants (PVs) in this gene, here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…A more recently published study in families with breast-ovarian cancer aggregation revealed the presence of five different large deletions in the BARD1 gene in five breast cancer patients. In two of the cases, there was a confirmed history of CRC among their relatives, but no data on cosegregation were provided [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A more recently published study in families with breast-ovarian cancer aggregation revealed the presence of five different large deletions in the BARD1 gene in five breast cancer patients. In two of the cases, there was a confirmed history of CRC among their relatives, but no data on cosegregation were provided [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1993 index cases from BRCAX families were included that had previously tested negative for pathogenic or likely pathogenic variants in the BRCA1, BRCA2, PALB2, ATM, CHEK2, BRIP1, RAD51C, and RAD51D genes, either with the NGS gene panel used here or with that described in Benito-Sánchez et al, 2022 [32]. Samples came from seven Spanish centers: Spanish National Cancer Center (CNIO) (Madrid, Spain), Hospital Clínico San Carlos (Madrid, Spain), Hospital General La Mancha Centro (Ciudad Real, Spain), Complejo Hospitalario Universitario de Albacete, Hospital General Universitario de Ciudad Real, Hospital Virgen de la Luz (Cuenca, Spain), and Laboratorio de Cáncer Hereditario of Instituto de Biología y Genética Molecular (Universidad de Valladolid, Valladolid, Spain).…”
Section: Brcax Casesmentioning
confidence: 99%